Polystyrene Plastic Waste Conversion into Liquid Fuel with Catalytic Cracking Process Using Al2O3 as Catalyst - Nurul Kholidah; Muhammad Faizal; Muhammad Said (Science and Technology Indonesia, 2018)
The increase in energy consumption and an increase in the plastic waste generation are two major problems that arise along with economic growth and the increase in population. Styrofoam is one type of polystyrene plastic waste that can be processed into liquid fuels by cracking process. In this study, the cracking process of polystyrene plastic waste into liquid fuel carried by the catalytic cracking process using Al2O3 as a catalyst. This study aimed to determine the effect of the catalyst weight, length of cracking time and range of temperature in the catalytic cracking process of polystyrene plastic waste into liquid fuel toward the mass and characteristics of liquid fuels produced and to determine the composition of liquid fuels produced. The catalytic cracking process of polystyrene plastic waste with catalyst was done in the fixed bed type reactor by heating the reactor with a heater, where the process took place at temperature of 150°C, 200°C, 250°C and 300°C and the length of the process was varied into 20, 40, and 60 minutes and the catalyst weight was also varied, which were 4%, 6% and 8%, while the styrofoam weight was 250 grams. From the research, the highest mass of liquid fuel derived from polystyrene catalytic cracking process was in the amount of 48.8 grams and liquid yield percentage of 19.5% at temperature of 250°C, cracking time of 60 minutes and weight of 8% catalyst, while the characteristics of liquid fuel that were approaching the characteristics of gasoline was at temperatures of 250°C, cracking time of 60 minutes and weight of 6% catalyst, in which each value of density of 0.763 g/ml, specific gravity of 0.778 and oAPI gravity of 50.2. While other liquid fuels obtained from the cracking of polystyrene were still within the tolerance range characteristic properties of gasoline. Liquid fuels produced from the catalytic cracking process was analyzed using a GC-MS, in which the analysis results indicated that liquid fuels were included in the gasoline fraction.